Typical Household Elasticity of Demand for Pharmaceuticals Across European States - Żółtaszek, Agata (Acta Universitatis Lodziensis. Folia Oeconomica, 2022)
According to the World Health Organisation (WHO), almost a billion people worldwide are at risk of falling into poverty due to out‑of‑pocket health spending, and pharmaceuticals are an integral part of this growing problem. The presented study aims to assess the price and income elasticity of demand for pharmaceuticals across European states over the period 2009–2019. The subject of the analysis is a typical household in each state. The analysis focuses on evaluating interactions in the light of economic growth, thus the results are cross‑referenced with the countries’ development groups to pinpoint any similarities and contrasts within and between clusters. The results indicate that households in underprivileged regions have a higher responsiveness to economic stimuli than in prosperous states. Both the income and price elasticities indicate the existence of unmet need for pharmaceuticals due to insufficient financial resources. Moreover, households’ responsiveness to income and price changes varies across time, states and affluence development groups.